Islamic Education in Contemporary Central Asia: Reviewing Ideas, Curriculum and Pedagogy - Hussain, Showkat (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The definition and function of Islamic education are still a hot debate in Central Asian Muslim societies. Islam is a significant characteristic of these societies, and the governments approach the idea more utterly. The entire region is earmarked by a distinctive aspect of Islamic civilization that shaped the political and socio-economic structure of this region. This distinction corresponds to a spectacular culture with much broader intellectual traditions rooted in Inner Asia than those of Iran and the Middle East. The study of Islam in Central Asia not only represents various socio-political issues but also discusses contemporary intellectual revival (Tajdid) in the Islamic education system. The Soviet imposition of the teaching of scientific atheism in public schools meant that there were virtually no educators who were familiar with secular, social scientific curricula and teaching methodologies on the study of religion. The lack of pedagogical tools for teaching social scientific approaches to religion led to the widespread view that religion can or should be understood only in doctrinal terms. Not surprisingly, critical and comparative approaches to the study of religion, still in a nascent stage of development, have not found much of a following. The extreme Salafist elucidations of Islam, as well as leaden approaches of traditional viewpoints, are also a challenge to Islamic education in Central Asia since 2005. In 2010, Central Asian scholars of Islam became aware of the potential dangers of an overly narrow religious education and regularly express these concerns due to the isolation of much of the region from prestigious centres of Islamic learning, including Jamiaal-Azhar of Egypt, Arab Institutions and reputed Indo-Pak religious seminaries. In the given context, this article assesses the contemporary discourse of Islamic education in Central Asian Muslim societies, as well as its socio-political implications and significant challenges for designing a balanced pedagogical framework in Islamic education.